An Analysis About Drugs Dealers - Harahap, Rabiyatul Adawiyah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research was motivated by two accused drugs dealers who came from Mandailing Natal who were caught by members of the Padangsidimpuan City Police on January 8, 2020 in Field I Tor Simarsayang with evidence of narcotics class I, type of marijuana weighing 250 kilograms and was sentenced by a judge with sanctions sentence of 20 years in prison. The purpose of this study is to determine the application of the panel of judges regarding material law in the decision, to determine the judge's considerations in imposing the penalty. and to find out how the perspective of Islamic criminal law is related to the decision No.177/Pid.Sus/2020/Pn/Psp. The research used in this research is field research which is qualitative in nature, namely research conducted by collecting primary and secondary data. Research data that becomes primary data is data obtained directly from research subjects, namely the results of interviews with the Padangsidimpuan City District Court judges and the defendants in in social institution of Padangsidimpuan. While the secondary legal materials for researchers were obtained from laws and regulations, books, articles, expert opinions, and other sources deemed relevant and related to this research. The data collection technique is done by interview, and documentation. The data is processed by identification, clarification and analysis techniques to obtain final conclusions. The results of this study are the application of material law in No.177/Pid.Sus/2020/Pn/Psp is involvement as a narcotics courier, conspiracy in narcotics couriers and evidence. As well as the consideration of the panel of judges in decision No.177/Pid.Sus/2020/Pn/Psp in imposing a 20-year sentence, there are two considerations, namely juridical considerations and non-juridical considerations, in which the juridical considerations consist of the demands of the public prosecutor, a memorandum of defense for the defendant, statements the defendant, the statements of the witnesses, and mitigating and aggravating and non-juridical matters are sociological aspects. So that in imposing a sentence, the judges really consider the sanctions that will be decided based on the facts in the trial.